OBSTÁCULOS BUROCRÁTICOS NA IMPLANTAÇÃO DA COBRANÇA PELO USO DA ÁGUA – ENFOQUE NO ESTADO DO PARANÁ - Silva, Gislaine do Rocio Rocha Simões da (2009)
This is the Decade of Water, celebrated within 2005 and 1015. Time to rethink and redefine values, as it is not any secret that all environmental issues have been deeply discussed, a general agreement of determining that the urgency in having repairing measures in order to avoid degradation and foment the Planet Natural Resources preservation requires the capacity of governments, companies and civil society, acting together and articulated. In 8th January 1997, it was implemented an integrated management systems of the Hydric resources fundamented in State Legislations and in the Law n.9.433. Through this Law, water became a public domain asset and a limited natural resource, having economic value, putting in evidence that all society, the government and the companies should understand it as a public asset, finite and of economic value. Under these conceptions, this study is based on the proposition of this Law, which induces the State, civil society and companies to articulate and join in a sustainable project regarding the use of water, considering economic, social, political and cultural aspects, done from local factors and its interaction and adequacy. Therefore, the aim of this study is to identify the obstacles which contribute to the difficulty of charging the use of water, as the Law 9.433/1997 states, under the State apparatus which promotes the public policies, seeking to answer to the question: “Are the obstacles which impede the wide and effective implementation of charging for the use of water related to the system of formation and action methods of the members of the River Basin Committees?”. To reach such purpose, it was necessary an interdisciplinary study of the natural sciences and cultural sciences, involving Hidrology, Politics, Economics, Society, Law and History. It has been adopted as a theorical framework the Complexity Theory, which has as one of its great exponents Morin, having chosen the documental study, bibliographic research, being this study conducted by the deductive and analytic method and by the approach of qualitative research. Having the theorical and documental knowledge about the economic value of water, it was investigated the effectiveness of Law n. 9.433/97, noticing how little it has been applied in Brazilian States. Only three out of the 26 existing in Brazil are making a charge, besides, the companies which would generate a higher value for the charging of use of water are those responsible for the Basic Sanitation. Being limited in the State of Paraná and delimiting the research at SANEPAR, it has been found out that the path to be walked is long for the effectiveness of the mentioned Law. The positioning of SANEPAR managers, linked to the slowness of decisions of the members of the River Basin Committees goes upon a burocratic and inefficient process. Such situation was analyzed regarding the conceptions of Max Weber about burocracy as Power tool, taking into account that the attachment between the Democratic State of Law and the environmental issue faces the obstacles created by burocracy in the mechanisms of participative action in the River Basin Committees.